Ischemic and Pharmacological Preconditioning - V. V. Likhvantsev; V. V. Moroz; O. A. Grebenchikov; Yu. I., Gorokhovatsky; Yu. V. Zarzhetsky; S. S. Timoshin; D. I. Levikov; V. L. Shaibakova (Общая реаниматология)
The review article deals with the problem of ischemic preconditioning, the universal physiological mechanism of cell protection from hypoxia. Preconditioning is the term used to describe a phenomenon of the enhanced tolerance of a cell to a damaging factor due to its preliminary effects of stressful stimuli. The article describes the phenomenon of ischemic preconditioning and summarizes the results of a study of the possible mechanisms of this effect in organs and tissues. It discusses the key role of the enzyme glycogen synthase 3fl in the regulation of the mitochondrial pore and that of the latter in the protection of a cell from hypoxia. Experimental data are given on the testing of different drugs as pharmacological agents that initiate/inhibit preconditioning. Reasons for the selective efficacy of some antihypoxants and antioxidants are analyzed in the context of the ischemic preconditioning theory. Conventional anesthetics and analgesics as potential inductors or inhibitors of the process in question are discussed. Key words: ischemic preconditioning, hypoxia, anesthetics, cyto-protection.